Influence of the inlet swirl velocity profile shape on swirl decay in laminar pipe flow. (26th July 2007) - Benim, A.C.; Gul, F.; Pasqualotto, E.
Role of the inlet swirl velocity profile shape on swirl decay in steady-state, incompressible, laminar pipe flow is computationally analysed. Two different integral parameters, namely the circulation and the swirl number are investigated as measures of the swirl level. It is observed that swirl decays at different rates along the pipe length, if the shape of the inlet swirl velocity profile is changed, although the inlet value of the integral parameter is kept constant. Even though this result is obtained for the laminar flow, it implies that a similar dependency may exist for the turbulent flow, and the accuracy of the swirl decay correlations may be increased, if they are additionally sensitised to the shape of the swirl velocity profile.